What kind of a constitutional crisis is Europe in and what should be done about it? - Mattias Kumm (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
The central cause for the crisis in Europe is not undisciplined spending by profligate states, but the asymmetric structural symbiosis between states and banks. Under the current European regime states are lenders of last resort for banks and banks are lenders of last resort for states. That symbiotic relationship must be loosened. Banks must be regulated in a way that ensures that the financial sector does not depend on massive taxpayer financed transfers. The ECB in cooperation with the ESM must function as a lender of last resort for states. Furthermore the public costs of bank-bailouts are to a significant extent the result of genuinely European risks, for which it would be appropriate to hold the European Union as a whole accountable. The mechanism through which to organize this European responsibility should not be inter-state transfer mechanisms, such as those foreseen by the ESM. Instead this money should be paid for by genuinely European funds, raised by European taxes or levies. And given the significant role of the Commission in monitoring national budgets, the case for having the European elections turn into a genuine competition for a European government has gotten even stronger.
Keywords: 320; Europe; crisis; states and banks; ECB; ESM; European Union; European Commission